A European volunteering experience in Colombia - Carabalí, Clemencia; Tenjo, Victoria; Salazar, Sandra Victoria (Revista Española de Desarrollo y Cooperación, 2023)
Two Colombian organizations, the Association of Afro-descendant Women of Northern Cauca-ASOM and the Adorable Religious, recount their work experience during the certification process in the EU Aid Volunteers Initiative, both for meeting the standards for managing European volunteering, such as the experience on forming local volunteer groups.